Gambaran Tumbuh Kembang Anak Bawah Dua Tahun (BADUTA) yang Memiliki Ibu Bekerja atau Tidak Bekerja di Kelurahan Bendogerit Kecamatan Sananwetan Kota Blitar - Qurrotu Ainii (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
In a child's life there are two processes that continue operating in growth and development, this process takes place interdependency which depend on each other.Experts say infant is a golden period, especially the age of 0-2 years old to reach 80% of the brain development. Lack affection of mother-first year of life have a negative impact on the upbringing of children. The purpose of this study was to determine the picture of the development-growing children under 2 years old who have working mothers or not working at the Village Bendogerit Sananwetan District of Blitar. Method :This study was a descriptive study. The samples were taken with quota sampling technique using pre-screening questionnaire instrument development and anthropometric assessment. Result : From the research, the growth of children under 2 years old with the mother does not work 100% had appropriate growth and growth of children under 2 years old 93.75% of working mothers have the appropriate growth. While the development of the child under 2 years old with the mother does not work 93.75% had appropriate growth and development of children under 2 years old 87.5% of working mothers have the appropriate development. Discussion: Thus, the conclusion drawn growing up baduta in Village Bendogerit, Sananwetan District of Blitar with the mother did not work better than the development of the child baduta with working mothers. In accordance with the conclusions that had been raised, researchers gave suggestions to further research to better focus on the factors that affect growth and development in the mother works, as well as advice for the child's mother always bring KMS and always filled by officers.